Individual productivity as a key to survival: An integrated structural model of self-regulation, self-motivation, and social cohesion in Thailand’s industrial workforce - Khaegkhan, Thanongsak; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of self-regulation (SR), self-motivation (SM), and social cohesion (SC) on individual productivity (IP) among industrial workers in Thailand. This research responds to the pressing need for organizations to improve workforce performance by focusing on intrinsic factors that support sustainable productivity growth. A quantitative approach was employed, with data collected from 498 workers across six major regions of Thailand and analyzed by SEM in LISREL. The analysis revealed that all three independent variables had statistically significant and positive effects on individual productivity, with SR demonstrating the strongest direct influence (β = 0.33), followed by SM (β = 0.31) and SC (β = 0.20). In addition, SM played a mediating role in the relationship between both SR and IP, as well as between SC and IP. The findings provide practical guidance for human resource management; training programs and HR policies should target these intrinsic factors to boost efficiency without additional labor costs, particularly in industrial sectors facing labor shortages and rising production cost pressures.